2011
DOI: 10.1186/1472-6874-11-24
|View full text |Cite
|
Sign up to set email alerts
|

The role of female hormones on lung function in chronic lung diseases

Abstract: BackgroundThe prevalence, morbidity, and mortality of inflammatory lung diseases such as asthma, chronic obstructive pulmonary disease (COPD) and cystic fibrosis (CF) are increasing in women. There is a dearth of data on the biological mechanisms to explain such observations. However, some large epidemiologic studies suggest that lung function fluctuates during the menstrual cycle in female patients with airways disease but not in women without disease, suggesting that circulating estradiol and progesterone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 82 publications
1
130
0
10
Order By: Relevance
“…However, there are certain findings on gender differences in pulmonary diseases discussing an involvement of female hormones. 27 Among chronic obstructive pulmonary disease patients, a beneficial effect of inhaled corticosteroids was especially noticeable in women 28 and estrogen receptor-alpha was identified as a potential drug target preventing from lung inflammation. 29 Even changes in exhaled NO concentrations due to cyclic estrogen and progesterone changes were reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are certain findings on gender differences in pulmonary diseases discussing an involvement of female hormones. 27 Among chronic obstructive pulmonary disease patients, a beneficial effect of inhaled corticosteroids was especially noticeable in women 28 and estrogen receptor-alpha was identified as a potential drug target preventing from lung inflammation. 29 Even changes in exhaled NO concentrations due to cyclic estrogen and progesterone changes were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormones also contribute to this phenomenon. Female sex hormones such as estrogen and 11 showed that female hormones increase the airway inflammation when exposed to the allergen, and the severity also fluctuates over the course of menstrual cycles. Estradiol has an important role to up-regulate the pro inflammatory cytokine and down-regulate the anti-inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…A menopauza előtt nagyrészt szisztémásan, de a perifériás szöveteken és az agyban is termelődő 2-hidroxiösztrogének hormonális aktivitása sokkal gyengébb, ugyanakkor a tumorsejtek proliferációját és az angiogenezist gátolják (3. ábra) [35]. A 2-hidroxi-ösztrogének kialakításáért a CYP1A1 enzim a felelős, ezek az ER-hez nem kötődnek, ezáltal kevésbé reaktívak [36,37]. Jelenleg is több klinikai vizsgálat zajlik, ahol a 2-metoxiösztradiol antiangiogenetikus, valamint antivascularisatiós hatását értékelik [38].…”
Section: Az öSztrogénmetabolitok Biológiai Hatásaiunclassified
“…A GPER lehet felelős a nem kanonikus ERmediált útvonal aktivitásáért. Emellett emelkedett 17β-HSD1-, valamint aromatázaktivitást találtak, amelyek részt vesznek az aktív ösztrogének lokális szintézi-sében [36,37].…”
Section: Az öSztrogénmetabolom Szerepe Tüdőtumorokban éS Copd Kialakuunclassified